Iterative Implicit Monte Carlo. Issue 1 (23rd February 2016) - Gentile, N. A.; Yee, Ben C.
ABSTRACT: We describe a new Monte Carlo thermal radiation transport method that is fully implicit in the value of matter temperature used to calculate thermal emission. This method involves iterating on the matter temperature until convergence at the end of the time-step value of the matter temperature is obtained. Because the method is fully implicit, it eliminates the violations of the maximum principle that can occur in Implicit Monte Carlo (IMC) simulations on the problems on which we have tested it. The method has the drawback that it is considerably more expensive than IMC for simulations with cold opaque regions. We discuss the reasons for this, and discuss some ways that the number of iterations may be reduced.